THE DEBRIS PARTICLES ANALYSIS OF RSG GAS COOLANT TO ANTICIPATE SEDIMENT INDUCED CORROSION - Sriyono Sriyono; Rahayu Kusumastuti; Sofia Loren Butarbutar; Abdul Hafid; Geni Rina Sunaryo; Diyah E. Lestari; Elisabeth Ratnawati (Jurnal Pengembangan Energi Nuklir, 2016)
THE DEBRIS PARTICLES ANALYSIS OF RSG-GAS COOLANT TO ANTICIPATE SEDIMENT-INDUCED CORROSION. The reliability of the structures, systems and components (SSC) of the G.A. Siwabessy Multipurpose Research Reactor (RSG-GAS) should be maintained to keep the reactor operates safely. Chemical control and management of coolant is one factor which determines the SSC’s reliability. The debris sedimentation in the primary coolant system must be examined. Debris occurs in the reactor pool, originating from airborne dust from the engineering hall. Several elements contained by the sediment can induce corrosion. This research was conducted to identify the trace elements which were contained in the sediments and determine their concentrations. The objective was to anticipate the occurrence of galvanic and pitting corrosion due to the presence of elements which are more noble than aluminum. The measurement methodology is Neutron Activation Analysis (NAA). Two groups of samples were analyzed; the first group was sampled from the debris trapped in the mechanical filter after the resin column, or known as the resin trap, and second was sampled from the debris which adhered to the heat exchanger tube. The primary coolant debris analysis showed that the neutron-activated sediment contained Na-24, Na-25, Al-28, Mg-27, Cr-51, Mn-54, Mn-56, Co-58, Co-60, Ni-65, and Fe-59. The Mn, Cr, Co, Ni, and Fe are more noble than aluminum can induce galvanic corrosion while Na, Ba, Al, and Mg are not. The radionuclides contained by the result of neutron activation of sediment from the heat exchanger tube are Mn-56, Na-24, As-76, Br-82, Fe-59, Zn-65, Cr-51, La-140, and Sc-46 which are mostly carbon steel corrosion products. Those elements do not initiate galvanic corrosion. The prevention of galvanic corrosion can be done by periodic maintenance.Key Words : sediment, debris, corrosion, galvanic, pitting, RSG Gas